2016
DOI: 10.5539/ibr.v9n6p131
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving the Credit Card Ownership in Italy

Abstract: The aim of this paper is to explore the main determinants of credit card ownership by analyzing the variables that may affect the decision to hold a credit card. Using the 2012 Survey on Household Income and Wealth provided by the Bank of Italy as main source, we estimated count data models in order to identify the socio-economic, demographic and territorial variables affecting the credit card accounts held by households. Our estimates give evidence of the significance of the considered factors. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On (ii), the assumption of a …xed mass of cardholders does not capture potential variations in the size of this group when the NSR is in force. Nevertheless, Kinsey (1981) and Amendola, Pellecchia and Sensini (2016) found that consumers'decisions to subscribe to a credit card can be broadly explained by reasons that are independent of the NSR, such as: income, place of residence, use of checking and savings accounts, attitude towards credit, age and occupation. Even considering elastic card adoption in the model, it is unclear how the mass of cardholders would vary by virtue of the NSR.…”
mentioning
confidence: 99%
“…On (ii), the assumption of a …xed mass of cardholders does not capture potential variations in the size of this group when the NSR is in force. Nevertheless, Kinsey (1981) and Amendola, Pellecchia and Sensini (2016) found that consumers'decisions to subscribe to a credit card can be broadly explained by reasons that are independent of the NSR, such as: income, place of residence, use of checking and savings accounts, attitude towards credit, age and occupation. Even considering elastic card adoption in the model, it is unclear how the mass of cardholders would vary by virtue of the NSR.…”
mentioning
confidence: 99%